창원시 산단지역 휘발성유기화합물 및 원소성분 거동 분석 - 최운선(Wunseon Choi); 장세경(Sekyung Jang); 이철우(Chul-Woo Lee); 박채형(Chaehyeong Park); 김문수(Moonsu Kim); 송명기(Myoungki Song); 배민석(Min-Suk Bae) (한국대기환경학회지(국문), 2020)
Air pollution has been well documented as a major public health issue for many areas of the world, as a growing body of pollutants increases the risks of numerous diseases. In particular, the industrial complex is of importance for human health related to the higher concentrations of toxic emission. PM2.5 mass, sisteen heavy metals and twenty one volatile organic compounds collected at four sampling sites around the Changwon Industrial Complex were analyzed using gas chromatography - mass spectrometery and inductive coupled plasma - mass spectrometery. The results show that the source emissions can mainly contribute to sampling sites based on diurnal patterns and conditional probability function analyses. Ratio of volatile organic compounds to toluene and pairwise correlation scatterplots between 1,3,5-trimethylbenzene and n-propylbenzene & 4-chlorotoluene indicate that volatile organic compounds was highly associated with human activities. The Measurement of hazardous air pollutant result can contribute to establish the emission strategies for reduction from the industrial areas. KCI Citation Count: 0